Critical Illness Insurances: Challenges and Opportunities for Insurers - Gatzert, Nadine; Mägebier, Alexander (Risk Management and Insurance Review, 2015)
Since the first introduction of critical illness insurance in 1983 in South Africa, the product has successfully spread to some insurance markets, especially in Asian and Anglophone countries, but market penetration remains low in other countries. For this reason and because of the increasing relevance of dread diseases, the aim of this article is to provide a first comprehensive overview of challenges and opportunities associated with critical illness products for insurers. Toward this end, we first present the various product designs, as well as the developments that have taken place within the market before comparing this form of coverage to alternative insurance products in order to better assess the market potential. Based on these assessments, we thoroughly discuss the major challenges and opportunities within the market from the insurer's perspectiv
Keywords: Critical illness insurance; dread disease market; health insurance; product design